Strategi Pemasaran Digital dan Payment Digital dalam Meningkatkan Penjualan Kebab Dara Cabang Lubuk Begalung - Ainul Qodri; Lara Sulmi Riva; Ramdani Bayu Putra; Wulandari Oktavia (JURNAL RISET MANAJEMEN DAN EKONOMI (JRIME), 2024)
This service activity aims to find out the application of digital marketing strategies and digital payments in increasing sales of Kebab Dara, Lubuk Begalung branch, Padang City, the obstacles faced by Kebab Dara in digital marketing and digital payments and the efforts made by Kebab Dara to increase sales of the products faced. In this activity we use detailed analysis using data collection techniques, observation and interviews. The results of this activity indicate that Kebab Dara is experiencing problems with declining sales. To overcome this, a digital marketing strategy is needed through social media such as Instagram, Facebook, TikTok and other social media and appropriate digital payments or qris so that sales can increase again in the future in an era of increasing numbers of competitors. After carrying out this research and observations, the marketing strategy carried out by Kebab Dara is a mix of digital marketing and digital payments.